Leveraging Educational Reforms for Poverty Alleviation in India: Comparative Insights from China’s Experience - Jitendra Kumar Sinha (Journal of Advanced Research in Economics and Business Management, 2024)
Poverty alleviation through education is a critical and sustainable strategy for rural revitalization. This study emphasizes the urgent need to evaluate the current state of rural education in India, identify existing challenges, and align educational initiatives with broader rural development goals. Key recommendations include Skill Development: Equip rural populations with relevant skills for industrial and agricultural jobs to enhance employability and economic stability. Investment in Education: Increase investments in basic and technical education to foster a skilled workforce aligned with national economic objectives. Economic-educational alignment: ensure educational initiatives are closely aligned with economic development strategies to promote mutual growth and prosperity. Cultural and Legal Awareness: Implement programs to advance cultural values, civility, and legal awareness, fostering a self-reliant and innovative populace. Entrepreneurship and Self-Improvement: Develop educational programs that promote entrepreneurship and self-improvement, particularly targeting the adult poor to enhance their employment prospects. Child Education and Future Deprivation: Prevent future deprivation of opportunities by ensuring that children in impoverished areas complete their education. Attracting Talent: Invest in creating quality educational environments to attract and retain high-quality talent in rural areas. Modernization and Integration: Modernize educational practices to support agricultural development, train new farmers, and integrate these efforts with national rural revitalization strategies. Sustained Focus on Rural Education: prioritize rural education even after poverty eradication to sustain agricultural modernization and long-term prosperity. Research and Policy Development: Promote research on the synergistic effects of education and poverty alleviation, develop coherent policies, and address rural-urban disparities in educational resources. Global Collaboration and Informatization: Promote educational informatization using advanced theories and international experiences, fostering collaboration for optimized education policies. By operationalizing these recommendations, India can strategically harness education as a pivotal mechanism for sustainable poverty alleviation and socio-economic advancement. This approach will enable the systematic development of human capital in rural areas, driving immediate economic gains and long-term socio-economic resilience. Ultimately, this framework fosters an environment conducive to sustained educational attainment, workforce readiness, and rural revitalization, securing India’s rural populace’s prosperous and self-sufficient future.